Defining the Performance Indicators: A Framework for Program Outcomes’ Attainment - Kotturshettar, B. B. (Journal of Engineering Education Transformations, 2015)
The attainment of Program Outcomes (PO) at the time of graduation is a measure of the competence of engineering graduates. The program outcomes are generic and have wide scope for interpretation by the faculty member depending upon his/her experience and judgment. Therefore, the attainment process might end up with either measuring too many things making the entire exercise very hectic or measuring too little that may not be sufficient to capture the intent of the outcome. Nowadays the practice is to expand each of the program outcomes into a set of outcome elements. As a result, the faculty members can use these elements in adapting the outcomes to their courses. Even with the elements being known, many a times it is a difficult proposition especially for the novice and in-experienced faculty members to plan their delivery and assessment mechanism. The reason being each element may involve several attributes or stages before it is fully understood. An attempt has been made to identify those logical stages as performance indicators for each of the outcome elements. Performance indicators provide faculty members with enough resolution for planning effective delivery and assessment modes leading to meaningful attainment of program outcomes.